Application of a Prognostic Stratification System for High-risk Prostate Cancer to Patients Treated With Radiotherapy: Implications for Treatment Optimization. (April 2019) - Foster, Benjamin; Jackson, William; Foster, Corey; Dess, Robert; Abu-Isa, Eyad; McLaughlin, Patrick William; Merrick, Gregory; Hearn, Jason; Spratt, Daniel; Liauw, Stanley; Hamstra, Daniel
Abstract : Objectives: We applied an established prognostic model to high-risk prostate cancer (HRPC) patients treated with radiotherapy (RT) and evaluated the influence of clinical and treatment variables on treatment outcomes. Methods: In total, 1075 HRPC patients undergoing definitive radiotherapy (RT) between 1995 and 2010 were retrospectively reviewed. Median follow-up was 62.3 months. Patients received either dose-escalated external beam radiotherapy (n=628, EBRT) or combined-modality radiotherapy (n=447, pelvic RT and low-dose rate brachytherapy boost, CMRT). 82.9% received androgen-deprivation therapy (ADT). A prognostic model stratified patients into predefined groups (good, intermediate, and poor). Kaplan-Meier methods and Cox proportional hazards regressions assessed biochemical failure (BF), distant metastasis (DM), prostate cancer-specific mortality (PCSM) and overall mortality (OM). C-indices analyzed predictive value. Results: The model was prognostic; C-indices for BF, DM, PCSM and OM were: 0.62, 0.64, 0.61, and 0.57. On multivariate analysis, CMRT and longer ADT (≥24 mo) were associated with improved BF, DM, and PCSM. Gleason score (GS) 9-10 was the strongest predictor of PCSM. C-indices for BF, DM, PCSM, and OM using a 4-compartment model incorporating GS 9-10 were: 0.62, 0.65, 0.68, and 0.56. In poor-prognosis patients (GS 8-10+additional risk factors), CMRT+LTADT (>12 mo) had 10-year PCSM (3.7%±3.6%), comparing favorably to 25.8%±9.2% with EBRT+LTADT. Conclusions: The model applies to high-risk RT patients; GS 9-10 remains a powerful predictor of PCSM. Comparing similar prognosis patients, CMRT is associated with improved disease-specific outcomes relative to EBRT. In poor-prognosis patients, CMRT+LTADT yields superior 10-year PCSM, potentially improving RT treatment personalization for those with HRPC. Abstract : Supplemental Digital Content is available in the text.